2004
DOI: 10.1186/1476-7120-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitral annulus calcification, aortic valve calcification with carotid intima media thickness

Abstract: Background: Mitral annular calcification (MAC) and aortic annular calcification (AVC) may represent a manifestation of generalized atherosclerosis in the elederly. Alterations in vascular structure, as indexed by the intima media thickness (IMT), are also recognized as independent predictors of adverse cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…According to other studies the value of IMT also increases linearly with the extent of valvular calcification [12].…”
Section: Discussionmentioning
confidence: 99%
“…According to other studies the value of IMT also increases linearly with the extent of valvular calcification [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies which investigated the relationship between fetuin-A and MAC. Sgorbini et al (28) observed a negative correlation between MAC and fetuin-A levels in a group of CAD patients with normal or mildly impaired renal functions. Supporting these results Ix et al (30) revealed a significant, negative association between MAC and serum fetuin-A level.…”
Section: Discussionmentioning
confidence: 97%
“…There are few studies investigating the association between MAC and CIMT. Sgorboni et al (28) showed that patients with MAC had higher CIMT measurements. In this pres- CIMT -carotid intima-media thickness, EDVR -endothelium-dependent vasodilatory response, hsCRP -high-sensitive C-reactive protein ent study MAC group had statistically higher levels of CIMT measurements than the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been reports of an association between mitral and aortic valve calcification and generalized atherosclerosis, mainly in elderly patients. 7,8 In these patients, carotid intima media thickness (cIMT) increases in parallel with the degree of valvular calcification score. 7 Patients undergoing heart valve surgery may also have a high prevalence of vascular risk factors (eg, hypertension, hyperlipidemia, diabetes mellitus, and smoking).…”
Section: Carotid Artery and Heart Valve Disease: A Common Occurrence?mentioning
confidence: 99%
“…7,8 In these patients, carotid intima media thickness (cIMT) increases in parallel with the degree of valvular calcification score. 7 Patients undergoing heart valve surgery may also have a high prevalence of vascular risk factors (eg, hypertension, hyperlipidemia, diabetes mellitus, and smoking). 9 Extrapolating from a population-based study of patients with carotid artery occlusion, 3 the vast majority of cardiovascular patients had at least 1 vascular risk factor.…”
Section: Carotid Artery and Heart Valve Disease: A Common Occurrence?mentioning
confidence: 99%